TFE3 Translocation–associated Perivascular Epithelioid Cell Neoplasm (PEComa) of the Gynecologic Tract: Morphology, Immunophenotype, Differential Diagnosis. (March 2015) - Schoolmeester, J. Kenneth; Dao, Linda N.; Sukov, William R.; Wang, Lu; Park, Kay J.; Murali, Rajmohan; Hameed, Meera R.; Soslow, Robert A.
Abstract : TFE3 translocation–associated PEComa is a distinct form of perivascular epithelioid cell neoplasm, the features of which are poorly defined owing to their general infrequency and limited prior reports with confirmed rearrangement or fusion. Recent investigation has found a lack of TSC gene mutation in these tumors compared with their nonrearranged counterparts, which underscores the importance of recognizing the translocated variant because of hypothetical ineffectiveness of targeted mTOR inhibitor therapy. Six cases were identified, and TFE3 rearrangement was confirmed by fluorescence in situ hybridization. Patient age ranged from 46 to 66 years (median 50 y), and none had a history of a tuberous sclerosis complex. Three cases arose in the uterine corpus, 1 in the vagina, 1 pelvic tumor, and 1 pulmonary tumor that was likely a recurrence/metastasis from a probable uterine primary. Five cases had clear cell epithelioid morphology that showed a spectrum of atypia, while 1 case had a mixture of clear cell epithelioid and spindle cells. A mostly consistent immunophenotype was observed in the clear cell epithelioid cases: each demonstrated diffuse TFE3, HMB45, cathepsinK labeling, either focal or no melanA staining, and variably weak reactivity to smooth muscle markers. The mixed clear cell epithelioid and spindle cell case had a similar expression pattern in its epithelioid component but strong muscle marker positivity in its spindle cell component. Follow-up ranged from 1 to 57 months. Three cases demonstrated aggressive behavior, and 3 cases had no evidence of recurrence. Both GYN-specific and traditional sets of criteria for malignancy were evaluated. The GYN model showed improved inclusion and specificity in comparison to the traditional model.